Having It Both ways: Clean Air Via Market Incentives An Examination of Internal Auditor Readiness - Ewer, Sid R (The International Journal of Accounting and Business Society, 1996)
This paper describes a small sample study of internal auditor responsiveness to The Clean air Act Amendment (CAA) of 1990 and the centerpiece of the Act, the Emission Allowance (EA) Program. The use of EAs represent an experiment by Congress to enhance corporate ï¬‚exibility in complying with one aspect of environmental legislation, lf the experiment proves successful, Congress will likely extend similar ï¬‚exibility in future pollution control initiatives. Corporations and their professional staff, therefore, in addition to the usual need of managing important assets that EAs represent, also have a public interest incentive to make more than a passing interest in this program. The results of the study indicate, however, that international auditors have not taken a proactive interest in the CAA of I990 and its EA program. lnternal auditors who attended the 1994 Seventh Annual National Utility Coal Conference were surveyed on various aspects of the Act was to become operational, their knowledge of and involvement in the issues related to the Act could only be characterized as moderate at best. In 1995, after one year of the Act being operational, the same internal audit organizations were surveyed. Changes were insigniï¬cant. As a result of the comparison between the l994 survey and the follow-up survey at the end of 1995, it was concluded that, rather than a proactive responsiveness on the part of the accounting profession as called for by some in the profession concerned about environmental matters, the response of internal auditors who are most immediately affected by this legislation would have to be characterized as conventional and reactive.